Coated sponge
By applying solid water-insoluble elastomer non-silicon polymer coating on the sponge surface, combined with phase change materials and ceramic particles, the tactile characteristics and performance problems of sponge in cosmetic application and removal are solved, and more efficient cosmetic transfer is achieved and lower product waste.
Patent Information
- Application Number
- CN202180024765.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-09
- Filing Date
- 2021-01-27
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-01-27
AI Technical Summary
When used for cosmetic application and removal, it is difficult to provide a method that has both good tactile characteristics and does not interfere with its basic functions. In the prior art, coating materials often have insufficient sliding resistance and thermal durability, which affects the use. Experience.
Using solid water-insoluble elastomer non-silicon polymer coatings, combined with encapsulated phase change material particles and ceramic particles, to form a coating with high kinematic viscosity and Williams plasticity values for sponge surfaces, enhancing it in cosmetics applications properties in coating and removal.
It significantly reduces sliding resistance, improves thermal cooling and thermal durability, provides a more comfortable tactile experience, while improving the efficiency of cosmetic transfer and reducing product waste.
Smart Images

Figure BDA0003865316910000141 
Figure BDA0003865316910000151 
Figure BDA0003865316910000152
Abstract
Description
[0001] The present invention relates to sponges useful for cosmetic applications, in particular sponges useful for applying and / or removing cosmetic compositions to the skin.
[0002] Sponges are commonly used to apply cosmetics to human skin, particularly the face and hands, and / or remove cosmetics therefrom, or otherwise cleanse human skin. Sponges can be natural types, but are more typically synthetic polymer foams, such as polyurethane or silicone polymer foams. Sponges are designed to be soft to enhance tactile properties and avoid skin irritation, and are hydrophilic so they absorb makeup and other cosmetics.
[0003] Tactile properties are very important to consumers, so methods that can impart desirable tactile properties to sponges are of great interest. Such methods must not unduly interfere with the ability of the sponge to perform its primary function, i.e., applying and / or removing cosmetics from the skin and / or cleansing the skin.
[0004] Various methods have been proposed to impart a cool feeling to wipes, tissues, and other facial products. Among these methods, there are those described in U.S. Patents Nos. 8,039,011, 8,894,814, and 9,545,365 and U.S. Published Patent Application 2014-0242127. These patents describe lotions applied to tissues or skin. The lotions contain phase change materials, such as low melting waxes and other low melting polymers. U.S. Patent No. 9,234,509 describes molded articles coated with polymer phase change materials that are bonded to a molded substrate by covalent bonding and entanglement mechanisms.
[0005] U.S. Published Patent Application No. 2016-223269 describes polymer films including polymer phase change materials.
[0006] WO 2017 / 210439 describes a polyurethane foam with a surface coating comprising an encapsulated phase change material. The foam is used as a bedding material, i.e. for mattresses, pillows and similar items. The surface coating imparts a "cool touch" feature, which is a desired point of sale feature for those products.
[0007] The present invention is an article comprising a natural or synthetic sponge and a cured coating of a solid water-insoluble elastomeric non-silicone polymer adhered to at least one surface of the sponge, the cured coating further comprising (i) at least one silicone polymer having a thermal conductivity of at least 1 million mm at 25°C. 2 / s kinematic viscosity and / or a Williams plasticity value of at least 30 measured according to ASTM 926; (ii) encapsulated phase change material particles, the phase change material having a melting or glass transition temperature of 25°C to 37°C, and optionally (iii) ceramic particles having a particle size of up to 50 μm, the silicone polymer accounting for 2.5 wt% to 30 wt% of the combined weight of the non-silicone polymer, the silicone polymer, the encapsulated phase change material particles and the ceramic particles, the encapsulated phase change material accounting for 10 wt% to 70 wt% of the combined weight of the non-silicone polymer, the silicone polymer, the encapsulated phase change material particles and the ceramic particles, and when present, the ceramic particles accounting for up to 25 wt% of the combined weight of the non-silicone polymer, the silicone polymer, the encapsulated phase change material particles and the ceramic particles.
[0008] The coated sponges are particularly useful in cosmetic applications, such as applying cosmetics to the skin and / or removing cosmetics from the skin. The coated sponges have tactile properties that are highly desirable in such applications and effectively transfer cosmetics to the skin. Similarly, the coated sponges can be used in medical applications involving applying drugs to the skin and / or removing foreign substances from the skin. The coated sponges are suitable for cleaning the skin.
[0009] In another aspect, the present invention is a coating composition that can be used to produce the aforementioned articles. The coating composition comprises a liquid phase, the liquid phase comprising water and / or one or more other compounds that are liquid at 23°C and have a boiling point of 40°C to 100°C at standard pressure; a water-insoluble elastomeric non-silicone polymer dispersed in the liquid phase in the form of particles or droplets; at least one silicone polymer dispersed in the liquid phase, the at least one silicone polymer having a diameter of at least 1 million mm at 25°C. 2 / s viscosity and / or a Williams plasticity value of at least 30 measured according to ASTM 926; encapsulated phase change material particles dispersed in a liquid phase; and optionally ceramic particles dispersed in the liquid phase, wherein the silicone polymer accounts for 2.5 wt% to 30 wt% of the combined weight of the non-silicone polymer, the silicone polymer, the encapsulated phase change material particles and the ceramic particles, the encapsulated phase change material accounts for 10 wt% to 70 wt% of the combined weight of the non-silicone polymer, the silicone polymer, the encapsulated phase change material particles and the ceramic particles, and when present, the ceramic particles account for up to 25 wt% of the combined weight of the non-silicone polymer, the silicone polymer, the encapsulated phase change material particles and the ceramic particles.
[0010] The present invention is also a method for preparing the coated sponge of the present invention, which method comprises applying the aforementioned coating composition to at least one surface of a natural or synthetic sponge to form a continuous or discontinuous film thereon, and curing the coating composition to produce a coating on at least one surface of the sponge.
[0011] The present invention also relates to a method for applying cosmetics or drugs to the skin, which method comprises applying the cosmetics or drugs to the coated natural or synthetic sponge of the present invention and bringing the coated natural or synthetic sponge with the applied cosmetics or drugs into contact with the skin, so that the cosmetics or drugs are transferred from the coated natural or synthetic sponge to the skin.
[0012] A sponge is a water-insoluble, flexible, porous material having an interconnected pore system open to at least one or more outer surfaces to which a coating is applied. The sponge may be a natural sponge, such as a member of the phylum Porosia, or a genus of the genus Luffa, such as Luffa aegyptiaca or Luffa acutangula. Alternatively, the sponge may be a non-natural porous material made of a polymer material, such as cellulose, polyurethane rubber, natural rubber, silicone polymer, homopolymer or copolymer of conjugated dienes (such as butadiene and / or isoprene homopolymer or copolymer, including butadiene-styrene polymer and isoprene-styrene copolymer), polychloroprene, homopolymer or copolymer of one or more acrylate monomers, such as methyl acrylate, ethyl acrylate, hydroxyethyl acrylate, butyl acrylate, etc.; homopolymer and / or copolymer of isobutylene; nitrile rubber; polysulfide rubber, silicone rubber; homopolymer or copolymer of chloroprene rubber, etc. The polymeric material may have a glass transition temperature of 0°C or less as measured by differential scanning calorimetry.
[0013] In some embodiments, the sponge (without coating) exhibits a moisture absorption time of 5 seconds or less, preferably 4 seconds or less at 23±2°C. The moisture absorption time is measured on a 5.08×5.08×2.54 cm skinless sample dried to constant weight. 3 mL of room temperature water is slowly dripped from a pipette onto the top surface of the sponge sample, and the amount of time required for the sponge to absorb the water is recorded as the moisture absorption time.
[0014] The sponge (without coating) may have a viscosity of, for example, at least 24 kg / m 3 , at least 32kg / m 3 , at least 36kg / m 3 or at least 40kg / m 3 The foam density may be, for example, up to 250 kg / m 3 , up to 200kg / m 3 or up to 175kg / m 3 .
[0015] The sponge (without coating) may exhibit an elongation at break of at least 50%, at least 75%, or at least 100%.
[0016] The sponge (without coating) may exhibit a compression force deflection (CFD) value at 40% compression of 0.4 kPa to 15.0 kPa, and more preferably 0.4 kPa to 10 kPa, 0.4 kPa to 5 kPa, 0.4 kPa to 2.5 kPa or 0.4 kPa to 1.5 kPa, as measured according to ISO 3386-1.
[0017] The sponge (without coating) may exhibit a resilience of at most 70%, at most 60%, at most 50%, at most 25%, at most 20%, at most 15%, or at most 10% in the ball rebound test of ASTM D-3574. In some embodiments, the sponge exhibits a resilience of 20% to 70%, 40% to 70%, or 50% to 70%.
[0018] In some embodiments, the sponge (without coating) exhibits a recovery time of at most 1 second, or at most 0.25 seconds, or at most 0.1 seconds. The recovery time for the purposes of the present invention is measured by compressing a 2.0 inch (5.08 cm) thick piece of sponge (4.0×4.0×2.0 inches, 10.16×10.16×5.08 cm) to 24% of its original thickness at room temperature, keeping the sponge under the compression for one minute and releasing the compressive force. The time required for the sponge to recover to 90% of its original thickness after releasing the compressive force is the recovery time. The recovery time is conveniently measured using a viscoelastic foam testing device (such as the RESIMAT 150 device (with factory software) of Format Messtechnik GmbH). In an alternative embodiment, the sponge (without coating) exhibits a recovery time of at least 1 second, or at least 2 seconds and at most 15 seconds, preferably at most 10 seconds.
[0019] The sponge (without coating) may exhibit an airflow of at least 0.8 L / s as measured by ASTM D3574 Test G. The airflow may be at least 1.2 L / s or at least 1.4 L / s, and may be, for example, at most 8 L / s, at most 6 L / s, or at most 4 L / s.
[0020] Polyurethane foams having the aforementioned properties and useful as sponges can be prepared using general methods, such as, for example, WO2017 / 210439, U.S. Pat. Nos. 4,365,025, 6,479,433, 8,809,410, 9,814,187, and 9,840,575, U.S. Published Patent Applications Nos. 2004-0049980, 2006-0142529, and 2016-0115387, and PCT / US2018 / 052323.
[0021] Sponges are usually small in size, with a diameter of e.g. 200 cm 3Or smaller, usually no larger than 100cm 3 or no larger than 50cm 3 In some embodiments, the thickness (smallest orthogonal dimension) is no greater than 3.81 cm, no greater than 2.54 cm, or no greater than 1.27 cm. The sponge can be molded, i.e., prepared in a mold having an internal geometry identical to the external geometry of the sponge. The sponge can be a cut sponge made by molding a larger sponge to the final size and geometry of the sponge.
[0022] The cured coating includes an elastomeric non-silicone polymer that is solid at room temperature (23°C) and insoluble in water. The elastomeric non-silicone polymer itself (i.e., in the absence of phase change material and ceramic particles) preferably has a glass transition temperature of no greater than 0°C as measured by differential scanning calorimetry and an elongation at break of at least 50% according to ASTM D412. For the purposes of the present invention, polymers having these properties are considered to be elastomers. The elastomeric non-silicone polymer itself may have a glass transition temperature of no greater than -15°C, no greater than -25°C, or no greater than -40°C. The elongation at break of the elastomeric polymer may be 100% or more.
[0023] Examples of suitable elastomeric non-silicone polymers include natural rubber and synthetic polymers, such as conjugated dienes, such as homopolymers and copolymers of butadiene and isoprene (such as styrene-butadiene rubber); homopolymers and copolymers of acrylate monomers, such as methyl acrylate, ethyl acrylate, hydroxyethyl acrylate, butyl acrylate, etc.; homopolymers and copolymers of isobutylene; nitrile rubber; polysulfide rubber; homopolymers and copolymers of chloroprene rubber; polyurethane rubber, etc. Preferred elastomeric non-silicone polymers include acrylate polymers, i.e., homopolymers and copolymers of one or more acrylate monomers, such as methyl acrylate, ethyl acrylate, hydroxyethyl acrylate, butyl acrylate, etc. Natural and / or synthetic latex foams are useful.
[0024] The elastomeric non-silicone polymer preferably comprises at least 15 wt%, at least 20 wt%, or at least 30 wt% of the combined weight of the non-silicone polymer, the silicone polymer, the encapsulated phase change material particles, and the ceramic particles. In some embodiments, the elastomeric non-silicone polymer comprises up to 75 wt%, up to 50 wt%, or up to 40 wt%, on the same basis.
[0025] The coating comprises (i) at least one silicone polymer having a thermal conductivity of at least 1 million mm2 at 25°C as measured according to ASTM 926. 2 / s kinematic viscosity and / or a Williams plasticity value of at least 30; (ii) encapsulated phase change material particles and optionally (iii) ceramic particles having a particle size of up to 50 μm. In some embodiments, the encapsulated phase change material and ceramic particles (when present) are embedded in the elastomeric non-silicone polymer.
[0026] Silicone polymers are characterized by polymer chains having alternating silicon and oxygen atoms. The silicon atoms are also bonded to organic groups. Silicone polymers have a molecular weight high enough to provide a flow rate of greater than at least 1 million mm2 at 25°C as measured by rotational shear rheometry. 2 / s kinematic viscosity. Suitable measuring devices are TA Dynamic Hybrid Rheometer or Anton Paar Modular Compact Rheometer equipped with a 25 mm diameter cone-plate geometry. The kinematic viscosity can be at least 5 million mm 2 / s, at least 10 million mm 2 / s or at least 25 million mm 2 / s, and can be, for example, up to 500 million mm 2 / s, up to 250 million mm 2 / s or up to 150 million mm 2 / s.
[0027] The organic groups bonded to the silicon atoms of the organosilicon polymer may be independently selected from hydrocarbon groups or halogenated hydrocarbon groups. Examples of these groups are: alkyl groups having 1 to 20 carbon atoms, such as methyl, ethyl, propyl, butyl, pentyl and hexyl; cycloalkyl groups, such as cyclohexyl and cycloheptyl; aryl groups having 6 to 12 carbon atoms, such as phenyl, tolyl and xylyl; aralkyl groups having 7 to 20 carbon atoms, such as benzyl and phenethyl; halogenated alkyl groups having 1 to 20 carbon atoms, such as 3,3,3-trifluoropropyl and chloromethyl. The organosilicon polymer may be a homopolymer, copolymer or terpolymer containing such organic groups. Examples include: homopolymers containing dimethylsiloxy units, homopolymers containing 3,3,3-trifluoropropylmethylsiloxy units, copolymers containing dimethylsiloxy units and phenylmethylsiloxy units, copolymers containing dimethylsiloxy units and 3,3,3-trifluoropropylmethylsiloxy units, copolymers of dimethylsiloxy units and diphenylsiloxy units, and interpolymers of dimethylsiloxy units, diphenylsiloxy units and phenylmethylsiloxy units, and the like.
[0028] The silicon-bonded organic groups of the organosilicon polymer may also be selected from alkenyl groups having 1 to 20 carbon atoms, such as vinyl, allyl, butenyl, pentenyl, hexenyl or dodecenyl. Examples include dimethylvinylsiloxy-terminated dimethylpolysiloxane, dimethylvinylsiloxy-terminated dimethylsiloxane-methylvinylsiloxane copolymer, dimethylvinylsiloxy-terminated methylphenylpolysiloxane; dimethylvinylsiloxy-terminated methylphenylsiloxane-dimethylsiloxane-methylvinylsiloxane copolymer.
[0029] The silicon-bonded organic groups of the organosilicon polymer may also be selected from various organic functional groups, such as amino, amido, mercapto or epoxy functional groups.
[0030] Silicone polymers may be linear, branched, or a mixture of linear and branched materials.
[0031] Two or more silicone polymers may be used in combination.
[0032] In some embodiments, the organosilicon polymer comprises at least one hydroxyl-terminated organosilicon polymer having a diameter of at least 10 million mm 2 / s, preferably 20 million mm 2 / s to 150 million mm 2 Such hydroxyl-terminated silicone polymer is preferably poly(dimethylsiloxane).
[0033] In some embodiments, the organosilicon polymer comprises at least one vinyl terminated organosilicon polymer having a diameter of at least 10 million mm 2 / s and preferably 20 million mm 2 / s to 200 million mm 2 The kinematic viscosity of the vinyl terminated silicone polymer is preferably poly(dimethylsiloxane). A specific example is divinyl polymethylsiloxane / polydimethylsiloxane copolymer.
[0034] In some embodiments, the organosilicon polymer includes (a) at least one kinematic viscosity of 10 million mm 2 / s to 75 million mm 2 / s poly(dimethylsiloxane) and (b) at least one kinematic viscosity greater than 75 million mm 2 / s and up to 200 million mm 2 / s, preferably up to 150 million mm 2 / s poly(dimethylsiloxane). In such embodiments, both silicone polymers (a) and (b) may be hydroxyl terminated; both may be vinyl terminated, and one may be hydroxyl terminated and the other may be vinyl terminated. In a specific embodiment, the silicone polymer is a poly(dimethylsiloxane) having a kinematic viscosity of 10 million mm 2 / s to 75 million mm 2 / s hydroxyl-terminated poly(dimethylsiloxane) and a kinematic viscosity greater than 7500 mm 2 / s and up to 200 million mm 2 / s, preferably up to 150 million mm 2 A mixture of vinyl terminated poly(dimethylsiloxane) of 1:1 / s.
[0035] The silicone polymer comprises 2.5 wt % to 30 wt % of the combined weight of the elastomeric non-silicone polymer, the silicone polymer, the encapsulated phase change material particles, and the ceramic particles (when present). In some embodiments, the silicone polymer comprises at least 7.5 wt % or at least 10 wt %, and in some embodiments, also on the same basis, may comprise up to 25 wt % or up to 20 wt %.
[0036] The encapsulated phase change material comprises a phase change material having a melting or glass transition temperature of 25°C to 37°C, which is contained in a shell. For the purposes of the present invention, the weight of the phase change material includes the weight of the shell. The shell may account for 5% to 25% of the total weight of the encapsulated phase change material, and the phase change material itself accounts for the remainder thereof, i.e., 75% to 95% by weight.
[0037] Phase change material can be or include any one or more of, for example, natural or synthetic waxes, such as polyethylene wax, beeswax, lanolin, carnauba wax, candelilla wax, small crown coconut wax, sugar cane wax, jojoba wax, cuticle wax, coconut wax, petroleum wax or paraffin. In some embodiments, phase change material is an alkane or any mixture of two or more of such alkanes with or including 14 to 30, especially 14 to 24 or 16 to 22 carbon atoms. In a specific embodiment, phase change material is or includes octadecane and / or eicosane. Phase change material preferably has a melting temperature of 25°C to 37°C, especially 25°C to 32°C or 28°C to 32°C.
[0038] The encapsulated phase change material may exhibit a heat of fusion of at least 50 joules / gram (J / g), at least 100 J / g, or at least 150 J / g, as measured by differential scanning calorimetry, in the temperature range of 25° C. to 37° C. The heat of fusion may be as much as 300 J / g or more, but more typically is at most 250 J / g or at most 200 J / g.
[0039] The shell material can be, for example, a polymeric material that has a melting or decomposition (if the polymeric material decomposes without melting) temperature of at least 50° C. and preferably at least 100° C. Examples of useful shell materials include cross-linked thermosetting resins such as cross-linked melamine-formaldehyde, cross-linked melamine, cross-linked resorcinol urea formaldehyde, and gelatin.
[0040] The encapsulated phase change material is in the form of particles. The particles may have a particle size of 100 nm to 100 μm, as measured by microscopy. In some embodiments, the particles have a particle size of at least 250 nm, at least 500 nm, at least 1 μm, or at least 5 μm and at most 75 μm or at most 50 μm.
[0041] Suitable methods for preparing encapsulated phase change materials are described, for example, in US Pat. Nos. 10,221,323 and 10,005,059.
[0042] Suitable encapsulated phase change materials can be obtained from Microtek Laboratories, Dayton, Ohio, US.
[0043] The encapsulated phase change material comprises 10 wt % to 70 wt % of the combined weight of the elastomeric non-silicone polymer, the silicone polymer, the encapsulated phase change material, and the ceramic particles (when present). In some embodiments, the encapsulated phase change material comprises at least 20 wt %, at least 30 wt %, or at least 40 wt % on the aforementioned basis, and up to 60 wt % or up to 50 wt % on the same basis.
[0044] The optional ceramic particles are characterized by being a non-metallic inorganic solid, typically at 23°C, and having a melting or decomposition (if the ceramic particles decompose without melting) temperature of at least 200°C. The ceramic material should be insoluble in water and other components of the coating composition used to coat the sponge. Ceramic materials are compounds of at least two chemical elements, at least one of which is non-metallic. The ceramic particles can be amorphous, semi-crystalline or crystalline, but do not undergo phase changes in the temperature range of 0°C to 50°C. The ceramic material preferably has a thermal conductivity of at least 50 W / (m×K) in at least one direction, as measured according to ASTM C1470. Examples of useful ceramic particles include boron nitride and silicon nitride, the boron nitride can be amorphous or in hexagonal, cubic and / or wurtzite form.
[0045] The ceramic particles have a particle size of at most 50 μm. Particle size herein refers to the longest dimension of the primary (non-agglomerated) particles, as determined using microscopic methods. The preferred minimum particle size is at least 100 nm, at least 250 nm or at least 500 nm. The preferred maximum particle size is at most 20 μm, at most 10 μm or at most 5 μm.
[0046] When present, the ceramic particles comprise up to 25 wt % of the combined weight of the elastomeric non-silicone polymer, the silicone polymer, the encapsulated phase change material particles, and the ceramic particles. In some embodiments, the ceramic particles comprise at least 2 wt % or at least 4 wt %, and also comprise up to 20 wt %, up to 15 wt %, or up to 10 wt %, on the same basis.
[0047] In some embodiments, the coating is prepared by forming an emulsion and / or dispersion of an elastomeric non-silicone polymer, an encapsulated phase change material, and (optionally) ceramic particles, applying the emulsion or dispersion to the surface of the sponge, and curing the emulsion to produce a cured coating. "Curing" is used herein to simply mean that the coating composition forms a solid coating by any mechanism or combination of mechanisms appropriate for the particular elastomeric non-silicone polymer present. It is not necessary for any chemical reaction (e.g., polymerization, cross-linking, or chain extension) to occur during the curing step, although such reactions may occur in some cases. Curing may simply involve drying the applied emulsion or dispersion to produce a solid coating.
[0048] The coating composition in the form of an emulsion or dispersion comprises a continuous liquid phase. The continuous liquid phase comprises water and / or one or more other compounds that are liquid at room temperature (23°C) and have a boiling temperature of 40°C to 100°C at standard pressure; such materials may account for, for example, 10% to 50% of the total weight of the coating composition. The elastomeric non-silicone polymer is dispersed in the continuous liquid phase in the form of particles or droplets. The silicone polymer is preferably dispersed in the continuous liquid phase in the form of droplets. Encapsulated phase change material particles and ceramic particles are also dispersed therein. The emulsion is preferably aqueous, that is, the continuous liquid phase comprises water. Preferably, the emulsion or dispersion comprises no more than 10% by weight, in particular no more than 5% by weight or no more than 2% by weight, of a room temperature liquid organic compound having a boiling temperature of 40°C to 100°C at standard pressure, based on the combined weight of such organic compounds and water.
[0049] The elastomeric non-silicone polymer may be provided in the form of an emulsion produced in an emulsion polymerization process wherein one or more monomers are dissolved or dispersed in a liquid phase and subjected to polymerization conditions until the polymer chains precipitate and convert into polymer particles dispersed in the liquid phase.
[0050] Similarly, an emulsion or dispersion of an elastomeric non-silicone polymer can be produced in a mechanical dispersion process, wherein a molten elastomeric non-silicone polymer is dispersed into a liquid phase and cooled to solidify the elastomeric non-silicone polymer.
[0051] In another suitable method, the elastomeric non-silicone polymer may be ground or otherwise formed into small particles which are then dispersed in a liquid phase.
[0052] The liquid phase of any such emulsion or dispersion of elastomeric non-silicone polymer may form part or all of the liquid phase of the coating composition.
[0053] The silicone polymer is preferably provided in the form of an emulsion in a liquid phase, preferably an aqueous liquid phase. Such an emulsion may contain, for example, 10% to 70% by weight, in particular 40% to 70% by weight of the silicone polymer, the remainder of the emulsion comprising water and one or more surfactants. Examples of such silicone polymer emulsions are described, for example, in WO 2012 / 018750 and WO 2019 / 081277. The surfactant is preferably nonionic. Ethylene oxide / propylene oxide block copolymers and ethoxylated fatty alcohols are examples of useful nonionic surfactants for such silicone polymer emulsions.
[0054] In such an emulsion of an organosilicon polymer, the organosilicon polymer is advantageously present in the form of droplets having a Dv50 of at most 20 μm. Dv50 refers to the droplet size when 50 volume percent of the droplets have the same or smaller diameter. In some embodiments, Dv50 may be at most 10 μm. In some embodiments, at least 90 volume percent of the droplets have a particle size of 100 nm to 10 μm.
[0055] The liquid phase of any such emulsion of silicone polymer may form part or all of the liquid phase of the coating composition.
[0056] The preferred form of the coating composition of the emulsion and / or dispersion is conveniently formed by combining an emulsion or dispersion of an elastomeric non-silicone polymer with a silicone polymer, encapsulated phase change particles and ceramic particles in the proportions as previously described. As previously described, the silicone polymer is also preferably provided in the form of an emulsion.
[0057] Such coating compositions may contain one or more optional materials in addition to those already described.
[0058] Among the optional materials useful are one or more hydrophilic polymers that are liquid at room temperature (23° C.) and have a weight average molecular weight of 350 g / mol to 8,000 g / mol, especially 350 g / mol to 1200 g / mol or 350 g / mol to 800 g / mol, as measured by gel permeation chromatography. The hydrophilic polymer is preferably water-soluble. Such hydrophilic polymers may contain at least 50% by weight or at least 75% by weight of ethylene oxide units, and may be, for example, a homopolymer of ethylene oxide or a copolymer of ethylene oxide (random and / or block) and one or other alkylene oxides, such as 1,2-propylene oxide. When present, such hydrophilic polymers may account for 0.1% to 15% of the combined weight of the hydrophilic polymer, the elastomeric non-silicone polymer, the silicone polymer, the phase change material and the ceramic particles. On the same basis, preferred amounts are at least 1 wt%, at least 2 wt%, at least 4 wt% or at least 5 wt% and at most 12 wt%, at most 10 wt% or at most 8 wt%.
[0059] Another useful optional material is one or more surfactants, which can perform one or more useful functions. Such surfactants can be used as wetting agents to promote the dispersion of phase change material particles and / or ceramic particles into the remaining components of the coating composition. Surfactants can be used as defoamers or degassing agents to reduce the entrainment of the gas of the coating composition and reduce bubbles. Various silicone surfactants and various non-silicone surfactants can be used for these purposes, such as sulfates, sulfonates, phosphates, ethoxylates, such as ethoxylated fatty alcohols, fatty acid esters, amine oxides, sulfoxides, ethylene oxide / propylene oxide block copolymers and phosphine oxides. Surfactants can be nonionic, anionic, cationic or zwitterionic. One or more surfactants can account for, for example, 0.1% to 5% by weight of the total weight of the coating composition. Surfactants present in the emulsion of silicone polymers can form all or part of the surfactants in the coating composition.
[0060] Other useful ingredients include various rheology modifiers, such as various thickeners and thixotropic agents. Among these are fumed silica and various water-soluble or water-swellable polymers of acrylic acid containing free acid groups or carboxylate groups (e.g., alkali metal, ammonium (NH 4 ), quaternary ammonium or quaternary phosphonium carboxylates). Particularly useful rheology modifiers include aqueous emulsions of crosslinked acrylic polymers, such as those sold by DuPont under the trade name A specific example is ASE-60 and Acrysol ASE-95 emulsions. When present, such rheology modifiers may comprise, for example, 0.01 wt % to 5 wt %, preferably 0.05 wt % to 1 wt % of the coating composition.
[0061] Still other useful ingredients include one or more colorants, preservatives, antioxidants and biocides.
[0062] The coating composition is conveniently prepared by mixing the foregoing ingredients. When the elastomeric non-silicone polymer is provided in the form of an emulsion or dispersion, it is convenient to combine the remaining ingredients with the emulsion or dispersion of the elastomeric non-silicone polymer in any convenient order to produce a homogenous dispersion.
[0063] A useful way to produce the coating composition of the present invention is to charge a portion of the liquid phase into a container. If a hydrophilic polymer is used, it is mixed with the portion of the liquid phase in the absence of the elastomeric non-silicone polymer and the silicone polymer. The ceramic particles (when used) are then combined with the portion of the liquid phase (and the hydrophilic polymer, if used) in the container, followed by the addition of the elastomeric non-silicone polymer (preferably in the form of an emulsion or dispersion), the silicone polymer (again preferably in the form of an emulsion), the encapsulated phase change material, and other ingredients in any convenient order.
[0064] The coating composition may be applied to at least one outer surface of the sponge. The coating method is not particularly critical. Rolling, brushing, spraying, dipping or other coating methods are suitable.
[0065] Sufficient coating composition is preferably applied so that, after curing, a cured coating having a thickness of from 100 μm to 10 mm is produced on at least one surface of the sponge. The coating thickness is preferably at least 250 μm or at least 350 μm and at most 2,500 μm, at most 1500 μm or at most 1000 μm. After drying, the coating may constitute, for example, from 1% to 25% of the combined weight of the coating and the sponge.
[0066] The coating on the outer surface of the sponge may be continuous, but is preferably discontinuous, such that at least some of the pores within the sponge remain open at the coated outer surface.
[0067] The inner surface of the sponge may be coated or uncoated. In some embodiments, no more than 25% or no more than 10% of the inner surface of the sponge is uncoated. In other embodiments, greater than 25% or greater than 50%, and up to 100% of the inner surface of the sponge is coated. As previously described, the coating is preferably discontinuous so that the pores in the sponge remain open at the coated outer surface.
[0068] The coating composition is cured on the surface of the sponge. The curing method may depend to some extent on the specific elastomeric non-silicone polymer and / or the physical form of the coating composition. Curing of the coating composition in the form of an emulsion includes at least one drying step to remove water and / or one or more other compounds that are liquid at room temperature (23°C) and have a boiling temperature of 40°C to 100°C at standard pressure, as may be present in the coating composition. Such drying step may be carried out at about room temperature, such as 15°C to 30°C, or at an elevated temperature, such as greater than 30°C up to 100°C or more.
[0069] If curing involves a chemical reaction (e.g., polymerization, crosslinking, or chain extension), the conditions of the curing reaction, such as temperature, the presence of co-reactants not otherwise present in the coating composition, catalysts, initiators, etc., are selected to promote the chemical reaction to achieve curing.
[0070] In some embodiments, the coated sponge exhibits a sliding resistance value (on the coated surface) of at most 50, at most 40, more preferably from 20 to 40 or from 30 to 40; a thermal cooling value of at least 4, preferably at least 5, especially from 5 to 10; and / or a thermal durability value of at least 3, at least 4 or at least 5 and preferably from 5 to 10, all values being calculated using Toccare Device (Syntouch Product Handbook, 21st edition, August 2018) at a temperature of 24°C to 25°C and a relative humidity of 40% to 50%. In some embodiments, the coated sponge exhibits a durometer line of up to 15 on the 00 scale as measured according to ASTM D2240. The presence of the coating is generally found to reduce sliding resistance and increase thermal cooling and thermal durability compared to uncoated sponges.
[0071] Furthermore, in some embodiments, such as using Measured in the same manner with the Toccare device, the coated sponges exhibited a tack value of less than 5. The presence of the coating was generally found to reduce this value compared to the uncoated sponge.
[0072] The coated sponge can be used to apply a cosmetic and / or pharmaceutical preparation to the skin. The cosmetic and / or pharmaceutical preparation can be, for example, a low viscosity liquid, a lotion, a cream, a gel, a paste or a powder. It is necessary that the preparation can be adsorbed and / or otherwise adhered to the coated sponge and then transferred from the sponge to the skin. Examples of such cosmetic and / or pharmaceutical preparations include antiperspirants and deodorants; skin care creams; skin care lotions; moisturizers; facial treatments, such as acne or wrinkle removers; personal and facial cleansers; bath oils; fragrances; colognes; sachets; sunscreens; pre-shave and after-shave lotions; shaving soaps and foams; hair shampoos; hair conditioners; hair colorants; hair relaxers; hair sprays; mousses; gels; long-lasting preparations; depilatories; cuticle paints; makeup; color cosmetics; foundations; concealers; rouge; lipsticks; eyeliners; mascaras; degreasers; makeup removers; powders; ointments; pastes or sprays, including anti-acne agents, dental hygiene agents, antibiotics, healing promoters, and nutrients, etc.
[0073] The coated sponge can be used to apply cosmetic and / or pharmaceutical preparations in a conventional manner. The cosmetic and / or pharmaceutical preparations can be applied to the coated sponge in any convenient manner suitable for the form of the formulated product. Dipping, immersion, rubbing, brushing, painting and other methods can be used. The coated sponge with the cosmetic and / or pharmaceutical preparation applied is then contacted with the skin to transfer the cosmetic and / or pharmaceutical preparation to the skin. Again, the contact method is not particularly critical and is generally suitable for the nature of the cosmetic and / or pharmaceutical preparation and the skin area to be applied.
[0074] Similarly, the coated sponge can be used to clean the skin in the same manner as an uncoated sponge. Dirt, foreign matter, cosmetics such as make-up, etc. can be removed, among many other things. The tactile properties of the coated sponge are very advantageous for this use.
[0075] The following examples are provided to illustrate the present invention and are not intended to limit the scope of the present invention. Unless otherwise indicated, all parts and percentages are by weight.
[0076] The degassing agent is a polyether siloxane copolymer with fumed silica, such as Tego Airex 904W from Evonik.
[0077] PEG is polyethylene glycol having an average nominal hydroxyl functionality of 2 and a number average molecular weight of approximately 600 g / mole.
[0078] Silicone Emulsion A is an aqueous emulsion containing hydroxyl-terminated polydimethylsiloxane, ethoxylated C11-15 secondary alcohol, and glycol-modified trimethylated silica. It is manufactured by The Dow Chemical Company under the trade name DowsilTM 52 sold. Hydroxyl terminated polydimethylsiloxane itself has a 30 million mm at 0.01 Hz and 25 ° C 2 / s dynamic viscosity, as measured by rotational shear rheometry using a TA dynamic mixing rheometer or Anton Paar modular compact rheometer equipped with a 25 mm diameter cone and plate geometry. The hydroxyl-terminated polydimethylsiloxane is present in the emulsion in the form of spherical droplets with a Dv50 equal to or less than 10 microns, as measured by laser diffraction with a fixed scattering angle of 90° or 180°. The emulsion contains about 65% by weight of polydimethylsiloxane.
[0079] Acrylic Emulsion A is an acrylic latex polymer emulsion with 55 wt% solids. The latex particles are T g is an elastomeric polymer at about -50°C. It is available from The Dow Chemical Company as E-1791 acquired.
[0080] Acrylic Emulsion B is an acrylic latex polymer emulsion with 55 wt% solids. The latex particles are T g is an elastomeric polymer at about -50°C. It is available from The Dow Chemical Company as 3166 obtained.
[0081] PCM 1 is a microencapsulated paraffin with a particle size of 15 μm to 30 μm. The wax accounts for 85%-90% of the weight of the material, and the polymer shell constitutes the remainder of the weight of the product. The wax has a melting temperature of about 32°C. The melting enthalpy of the product is 160 J / g-170 J / g. The product can be commercially obtained from Microtech Laboratories as MPCM 32D.
[0082] PCM 2 is a microencapsulated paraffin with a particle size of 15 to 30 μm. The wax accounts for 85% to 90% of the weight of the material, and the polymer shell accounts for the remainder of the product weight. The wax has a melting temperature of about 28°C. The melting enthalpy of the product is 180 J / g-190 J / g. The product can be commercially obtained from Microtech Laboratories as MPCM 28D.
[0083] PCM 3 is a 70% solids slurry of PCM 1 in diluent.
[0084] RM (rheology modifier) 1 is an aqueous emulsion containing crosslinked acrylate particles with acid groups. The solid content is 28%. When diluted with water and treated with a base (NH 4 OH), this product acts as a thickener.
[0085] RM 2 is an aqueous emulsion containing crosslinked acrylate particles with acid groups. The solids content is 18%. When diluted with water and treated with an alkali (NH 4 OH), this product acts as a thickener.
[0086] NH 4 OH is a 28%-30% ammonium hydroxide solution used to neutralize RM 1 and / or RM 2.
[0087] BN is boron nitride (at least 98% pure) in flake form with a longest dimension of about 1 μm to 3 μm, available from Wego Chemical.
[0088] Silicone Emulsion B is a nonionic emulsion comprising 60% of a divinyl polydimethylsiloxane / polydimethylsiloxane copolymer having terminal vinyl groups, a C 11-15 Ethoxylated mixtures of linear alkanols and C 11-15 Ethoxylated mixture of linear alkanols. Divinyl dimethicone / dimethicone copolymer itself has a molecular weight of at least 120 million mm at 0.01 Hz and 25°C. 2 / s dynamic viscosity, as measured by rotational shear rheometry using a TA dynamic mixing rheometer or Anton Paar modular compact rheometer equipped with a 25 mm diameter cone and plate geometry, and in the form of spherical droplets with a Dv50 particle size of 0.6 μm in the emulsion, as measured by laser diffraction with a fixed scattering angle of 90° or 180°. The product is available as Dowsil TM HMW 2220 nonionic additive is sold commercially.
[0089] Coating compositions 1 and 2 were prepared using the ingredients listed in Table 1 by mixing them in a high speed laboratory mixer to produce a homogeneous mixture.
[0090] Table 1
[0091]
[0092]
[0093] 1 Based on combined weight of elastomeric polymer, PCM, BN and silicone.
[0094] The coating compositions were each used to produce a coating on a commercially available polyurethane cosmetic sponge. The sponge was sold as the Aesthetica Body Sponge, which had flat sides and an oval shape before coating. It weighed approximately 13.75 grams, had a thickness of approximately 2 cm, and a foam density of approximately 0.17 g / cm 3 Its volume is about 81cm 3 The sponge is resilient and bounces back quickly when compressed. It has open pores and no cuticle.
[0095] In each case, 2.75 grams to 3 grams of the coating composition were applied to one flat surface of the sponge and spread evenly over the surface using a flat blade. The applied coatings were cured by heating the coated sponges at 80° C. for 60 minutes. Coating 1 was more viscous and blocked many of the surface pores. Coating 2 did not block the pores on the coated surface.
[0096] use Toccare device (Suntouch, Montrose, CA) evaluates the sliding resistance, thermal cooling and thermal persistence of the coated surface and the relative uncoated surface, and it reports the value of each attribute in a relative scale. Tested at a temperature of 24°C to 25°C and a relative humidity of 47% to 48%. Five points on the sample midline (the line dividing the sample test plane along the length of the longest dimension) are measured. For the expected cosmetic application, lower sliding resistance values are preferred, while higher thermal cooling and thermal persistence values are preferred. The results are shown in Table 2.
[0097] Table 2
[0098]
[0099] By applying the coating to the sponge surface, all three metrics were significantly improved. The sliding resistance values dropped by 10 units or more. Changes of this magnitude are easily perceived by human users.
[0100] An increase in the thermal cooling and thermal persistence values indicates a stronger desired "cool" feeling and a longer duration of that feeling. The magnitude of these increases makes them perceptible to a human user.
[0101] A cylindrical sponge sample with a diameter of 2.54 cm, a length of 2 cm and a weight of 1.78 ± 0.02 g was punched out from an uncoated sample of the same cosmetic sponge. The sponge sample was immersed in one or another coating composition described in Table 1 and then hung in an oven at 80° C. for 60 minutes to dry. The weight of the coated and dried sponge sample was 2.02÷0.15 g, corresponding to a coating of about 12% by weight. The coating covered substantially all of the outer surface of the sponge with little penetration into the inner surface. The pores of the sponge remained open and interconnected.
[0102] The coated sponge samples were then immersed in liquid makeup (L'Oreal True Match TM Nude BeigeSuper-Blendable Makeup Titanium Dioxide Sunscreen) for 5 seconds, removed, and allowed excess liquid makeup to drip from the sponge sample for 5 seconds. Each sample was then weighed to determine the amount of makeup absorbed. The sample was then compressed 25% (to 1.5 cm thickness) using a manual plunger equipped with a pressure distribution plate for 5 seconds to expel the makeup and weighed again to determine the amount of makeup released. Uncoated sponge samples were evaluated in the same manner for comparison. The results are shown in Table 3.
[0103] Table 3
[0104]
[0105] As can be seen, the coated sponges are significantly more effective at transferring makeup. While the uncoated sponges absorbed more makeup, they transferred less, retaining about two-thirds of the absorbed makeup. The coated sponges absorbed less makeup but transferred more, releasing more than half of the absorbed makeup. The coated sponges consumed about one-third less makeup product when applying the same amount of makeup as the uncoated sponges, thereby greatly reducing the amount of wasted product.
Claims
1. An article comprising a natural or synthetic sponge and a cured coating of a solid water-insoluble elastomeric non-silicone polymer adhered to at least one surface of the sponge, the cured coating further comprising (i) at least one silicone polymer having a thermal conductivity of at least 1 million mm at 25°C. 2 / s kinematic viscosity and / or a Williams plasticity value of at least 30 measured according to ASTM 926, wherein the silicone polymer has a polymer chain of alternating silicon and oxygen atoms, the silicon atoms also being bonded to organic groups, wherein the organic groups are independently selected from hydrocarbon groups or halogenated hydrocarbon groups; (ii) encapsulated phase change material particles, the phase change material having a melting or glass transition temperature of 25°C to 37°C, and optionally (iii) ceramic particles having a particle size of up to 50 μm, the silicone polymer comprising 2.5% by weight of the combined weight of the non-silicone polymer, the silicone polymer, the encapsulated phase change material particles and the ceramic particles to 30 weight percent, the encapsulated phase change material comprises 10 weight percent to 70 weight percent of the combined weight of the non-silicone polymer, the silicone polymer, the encapsulated phase change material particles and the ceramic particles, and when present, the ceramic particles comprise up to 25 weight percent of the combined weight of the non-silicone polymer, the silicone polymer, the encapsulated phase change material particles and the ceramic particles, wherein the non-silicone polymer is a homopolymer or copolymer of a conjugated diene; a homopolymer or copolymer of an acrylate monomer; a homopolymer or copolymer of isobutylene; a nitrile rubber; a polysulfide rubber; or a homopolymer or copolymer of chloroprene rubber. 2 . The article of claim 1 , wherein the cured coating has a thickness of 100 μm to 2500 μm.
3. The article of claim 1 or 2, wherein the phase change material comprises any one or more of natural or synthetic waxes.
4. The article according to claim 1 or 2, wherein the organosilicon polymer comprises (a) at least one kinematic viscosity of 10 million mm 2 / s to 75 million mm 2 / s poly(dimethylsiloxane), (b) at least one kinematic viscosity greater than 75 million mm 2 / s and up to 200 million mm 2 / s of poly(dimethylsiloxane), or a mixture of (a) and (b).
5. The article according to claim 1 or 2, wherein the organosilicon polymer has a kinematic viscosity of 10 million mm 2 / s to 75 million mm 2 / s of hydroxyl-terminated poly(dimethylsiloxane) and a kinematic viscosity greater than 75 million mm 2 / s and up to 200 million mm 2 / s of a mixture of vinyl terminated poly(dimethylsiloxane).
6. The article according to claim 1 or 2, wherein the ceramic particles are present and are boron nitride or silicon nitride particles having a particle size of 100 μm to 3000 μm.
7. The article of claim 1 or 2, wherein the phase change material comprises 30% to 50% of the combined weight of the elastomeric non-silicone polymer, silicone polymer, encapsulated phase change material particles, and ceramic particles.
8. The article of claim 1 or 2, wherein the ceramic particles comprise 4% to 15% of the combined weight of the elastomeric non-silicone polymer, silicone polymer, encapsulated phase change material particles, and ceramic particles.
9. The article of claim 1 or 2, wherein the silicone polymer comprises 10% to 20% of the combined weight of the elastomeric non-silicone polymer, silicone polymer, encapsulated phase change material particles, and ceramic particles.
10. The article of claim 1 or 2, wherein the cured coating further comprises a hydrophilic polymer that is liquid at 23°C and has a weight average molecular weight of 350 to 8000, wherein the hydrophilic polymer accounts for 0.1% to 15% of the total weight of the elastomeric polymer, encapsulated phase change material particles, ceramic particles and hydrophilic polymer.
11. The article of claim 1 or 2, wherein the conjugated diene is butadiene or isoprene.
12. The article according to claim 1 or 2, wherein the homopolymer or copolymer of a conjugated diene is styrene-butadiene rubber.
13. The article of claim 1 or 2, wherein the phase change material comprises any one or more of polyethylene wax, beeswax, lanolin, carnauba wax, candelilla wax, cocoa wax, sugarcane wax, jojoba wax, cuticle wax, coconut wax, petroleum wax or paraffin wax; and / or The organosilicon polymer comprises (a) at least one 2 / s to 75 million mm 2 / s poly(dimethylsiloxane), (b) at least one kinematic viscosity greater than 75 million mm 2 / s and up to 150 million mm 2 / s of poly(dimethylsiloxane), or a mixture of (a) and (b).
14. A coating composition comprising a liquid phase comprising water and / or one or more other compounds which are liquid at 23°C and have a boiling point of 40°C to 100°C at standard pressure ; A water-insoluble elastomeric non-silicone polymer dispersed in the liquid phase in the form of particles or droplets; at least one silicone polymer dispersed in the liquid phase, the at least one silicone polymer having a surface area of at least 1 million mm at 25°C 2 / s viscosity and / or a Williams plasticity value of at least 30 measured according to ASTM926; encapsulated phase change material particles dispersed in the liquid phase; and ceramic particles dispersed in the liquid phase, wherein the silicone polymer comprises 5 wt % to 30 wt % of the combined weight of the non-silicone polymer, silicone polymer, encapsulated phase change material particles and optional ceramic particles, the encapsulated phase change material comprises 10 wt % to 70 wt % of the combined weight of the non-silicone polymer, silicone polymer, encapsulated phase change material particles and ceramic particles, and when present, the ceramic particles comprise up to 25 wt % of the combined weight of the non-silicone polymer, silicone polymer, encapsulated phase change material particles and ceramic particles, wherein the non-silicone polymer is a homopolymer or copolymer of a conjugated diene; a homopolymer or copolymer of an acrylate monomer; a homopolymer or copolymer of isobutylene; a nitrile rubber; a polysulfide rubber; or a homopolymer or copolymer of chloroprene rubber, The organosilicon polymer has a polymer chain of alternating silicon and oxygen atoms, the silicon atoms also being bonded to organic groups, wherein the organic groups are independently selected from hydrocarbon groups or halogenated hydrocarbon groups.
15. The coating composition according to claim 14, wherein the phase change material comprises any one or more of polyethylene wax, beeswax, lanolin, carnauba wax, candelilla wax, carnauba wax, sugarcane wax, jojoba wax, cuticle wax, coconut wax, petroleum wax or paraffin wax, the ceramic particles are present, and the ceramic particles are boron nitride or silicon nitride particles having a particle size of 100 μm to 3000 μm.
16. The coating composition according to claim 14 or 15, further comprising a hydrophilic polymer that is liquid at 23°C and has a weight average molecular weight of 350 to 8000, wherein the hydrophilic polymer accounts for 0.1% to 15% of the total weight of the elastomeric polymer, encapsulated phase change material particles, ceramic particles and hydrophilic polymer.
17. The coating composition according to claim 14 or 15, wherein the conjugated diene is butadiene or isoprene.
18. The coating composition according to claim 14 or 15, wherein the homopolymer or copolymer of conjugated diene is styrene-butadiene rubber.
19. A method for preparing a coated sponge, the method comprising applying a coating composition according to any one of claims 14 to 18 to at least one surface of a natural or synthetic sponge to form a film thereon, and curing the coating composition to produce a coating on at least one surface of the sponge.
